Prevention of Bortezomib-Induced Polyneuropathy in Multiple Myeloma Patients - Garrido, David; Riva, Eloisa (Journal of Hematology Research, 2020)
Bortezomib (Velcade®) is a proteasome pathway inhibitor that has improved multiple myeloma (MM) overall survival. Bortezomib-induced peripheral neuropathy (BIPN) is a frequent adverse event, requiring delay, dose reduction or cessation of therapy. Although most of the symptoms resolve after discontinuation or dose-reduction, almost 25% develop chronic symptoms, affecting quality of life and limiting the therapeutic choices. There is limited evidence regarding the strategies to prevent bortezomib-induced polyneuropathy (BIPN). We conducted a review of the published data to summarize the available information regarding BIPN prevention strategies. Our search included literature published in the Cochrane Library databases, Medline/PubMed, SciELO, Google Scholar, and Trip Database in the last ten years, including observational analytic studies, experimental studies, systematic reviews, and metanalysis, which reported the efficacy of interventions to prevent BIPN. Eight studies have been included. The subcutaneous administration of bortezomib has shown a protective effect of all grades of BIPN (OR=0.40, 95% CI 0.27 to 0.59, p<0.001) and grade 3 to 4 (OR = 0.45, 95% CI 0.25 to 0.82, P<0.05), as evidenced in a metanalysis. Cumulative dose of bortezomib > 30 mg/m2 is significantly associated with a higher risk of BIPN. Other therapies as Acetyl-l-carnitine (ALC), dexamethasone in partnered dosing (day of/after bortezomib), high-dose intravenous mecobalamin (HDIME), and the combination of docosahexaenoic acid, α-lipoic acid, vitamin C 60 mg, and vitamin E have been assessed but their efficacy for BIPN prevention has not been confirmed. We conclude that the subcutaneous route of administration of bortezomib effectively prevents BIPN while other strategies lack robust evidence to be recommended.